Pengaruh Profitabilitas, Ukuran Perusahaan dan Struktur Modal terhadap Nilai Perusahaan - Sari, Diah Sudika; Mutia, Agutina; Sudharyati, Neneng (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this research is to find out whether profitability, company size and capital structure have an effect on company value. The population in this research are restaurants, hotels and tourism sub-sector companies that have sharia shares and are listed on the Indonesia Stock Exchange in 2020-2022. This research is quantitative research. Using the documentation data collection method, sampling was carried out using the purpose sampling method, and a sample of 14 companies was obtained. Company data was obtained from the official website of the Indonesian Stock Exchange. The analysis method used is panel data regression analysis with the help of the R Studio application. The research results show that partial profitability (ROA) has no effect on company value, company size (LN) partially has a negative and significant effect on company value and capital structure (DER) partially has a positive and significant effect on company value. Simultaneously, the variables profitability, company size and capital structure have a significant effect on company value.